(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
K-frames were recently introduced by Găvruţa in Hilbert spaces to study atomic systems with respect to a bounded linear operator. K-g-frames are more general than of g-frames in Hilbert spaces.Results on k-g- frames have been proved through operator- theoretic results of bounded operators.